Longitudinal and geographic variations in the green moisture content and basic density of bamboo culm in three species naturally grown in Lombok Island, Indonesia - Rini, Dwi Sukma (2022)
Longitudinal and geographic variations in the green moisture content and basic density of bamboo culm were evaluated by using linear mixed-effect models for three bamboo species (Bambusa vulgaris Schrad. ex J.C., Bambusa maculata Widjaja, and Gigantochloa atter (Hassk) Kurz ex Munro) naturally grown in four locations in Lombok Island, Indonesia. The mean green moisture contents and basic densities were 74.2 and 0.69 g cm-3 for B. vulgaris, 78.5 and 0.65 g cm-3 for B. maculata, and 80.3 and 0.65 g cm-3 for G. atter, respectively. No significant differences in green moisture content and basic density were found among the species. A significant negative correlation between basic density and green moisture content was found in all three species. Based on the results of model selections for longitudinal variations, the green moisture content decreased with an increase in the culm height in all three species, and basic density tended to increase from the base to the top of the culm. Relatively large geographical variation was found in the green moisture content and basic density of G. atter, although the main reasons for variation of these properties were individual culm in three species. © 2022 Japan Society of Tropical Ecology. All Rights Reserved.